Anxiety severity in peri‐adolescents is associated with greater generalization of negative memories following a period of sleep relative to wake. - Eihentale, Liga; Kimbler, Adam; Sollenberger, Nathan A.; Cummings, Logan R.; Yeguez, Carlos E.; Patriarca, Guadalupe C.; Pettit, Jeremy W.; McMakin, Dana L.; Mattfeld, Aaron T. (Journal of Child Psychology & Psychiatry, 2025)
Background: Sleep may facilitate preferential selection and reactivation of emotional information for memory consolidation, contributing to negative overgeneralization (i.e., an increased tendency to generalize negative information) in anxious individuals. We examined two aspects of emotional memory—recognition and generalization—in peri‐adolescents across a spectrum of anxiety severity using a sleep–wake design. We hypothesized that anxiety severity would interact with sleep to increase recognition and generalization of negative stimuli. Methods: Thirty‐four participants (16 females; mean age = 11.4, SD = 2.0) completed an emotional memory similarity task with a 10‐ to 12‐h sleep or wake retention interval, monitored by actigraphy and daily diary. Participants rated the valence (negative, neutral, positive) of images at encoding. During a recognition test, they identified targets (previously seen images), lures (images similar to targets), and foils (new images). Results: A mixed‐effects model showed a significant three‐way interaction between anxiety severity (PARS‐6), valence, and group (b =.011, SE =.005, p =.042). For negative valence, the effect of anxiety was significant in the sleep group (b =.013, p <.001) but not in the wake group (b =.0004, p =.927), with the slopes differing significantly (b = −.013, p =.020). In the sleep group, the negative slope was significantly greater than neutral (b = −.012, p =.002) but not positive (b =.007, p =.128). Slopes for neutral valence were not significant in either group (all ps >.05). Target recognition and lure discrimination interaction models were not significant. Conclusions: We provide evidence that anxiety severity in peri‐adolescents is associated with greater generalization of emotional—particularly negative—content following sleep compared to wakefulness. Sleep‐related emotional memory consolidation may contribute to negative overgeneralization, an etiological feature of anxiety disorders and a potential mechanism of change. Further investigation is warranted, especially during sensitive developmental periods like peri‐adolescence.